2009
DOI: 10.1088/0004-6256/137/5/4412
|View full text |Cite
|
Sign up to set email alerts
|

No Excess of Rr Lyrae Stars in the Canis Major Overdensity

Abstract: Our multi-epoch survey of ∼ 20 sq. deg. of the Canis Major overdensity has detected only 10 RR Lyrae stars (RRLS). We show that this number is consistent with the number expected from the Galactic halo and thick disk populations alone, leaving no excess that can be attributed to the dwarf spheroidal (dSph) galaxy that some authors have proposed as the origin of the CMa overdensity. If this galaxy resembles the dSph satellites of the Milky Way and of M31 and has the putative M V ∼ −14.5, our survey should have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 62 publications
2
46
0
Order By: Relevance
“…Mateu et al 2009) have questioned this due to the lack of blue horizontal branch stars in the CMa CMD compared to this and other clusters also potentially associated with the CMa overdensity, such as NGC 1851, NGC 2298 and NGC 2808. Further study of these clusters is therefore crucial to improving our understanding of the structure of the Galactic disc, as Martin et al (2004) also suggested that CMa is made up of a mixture of thin and thick disc and spiral arm populations of the Milky Way.…”
Section: Introductionmentioning
confidence: 93%
“…Mateu et al 2009) have questioned this due to the lack of blue horizontal branch stars in the CMa CMD compared to this and other clusters also potentially associated with the CMa overdensity, such as NGC 1851, NGC 2298 and NGC 2808. Further study of these clusters is therefore crucial to improving our understanding of the structure of the Galactic disc, as Martin et al (2004) also suggested that CMa is made up of a mixture of thin and thick disc and spiral arm populations of the Milky Way.…”
Section: Introductionmentioning
confidence: 93%
“…Miss-classification of the type c stars is a non-negligible possibility because if there are relatively few epochs in the light curves, eclipsing binaries of the type W UMa may mimic the shape of type c RR Lyrae stars. The contamination due to this type of stars is higher at lower galactic latitude, for example, when the disk population is large (see Vivas et al 2004;Mateu et al 2009, for a complete discussion). High-amplitude δ Scuti stars, which are also more common in the disk population, may have periods as long as type c stars, which makes them an additional source of A15, page 6 of 11 contamination.…”
Section: Comparison With the Properties Of The Cluster Rr Lyrae Starsmentioning
confidence: 99%
“…The former are easily detectable thanks to their brightness and characteristic light curves (see e.g. Mateu et al 2009;Prior et al 2009). The latter are about 3.5 mag fainter than RR Lyrae stars but at least 100 times more abundant.…”
Section: The Survey Strega@vstmentioning
confidence: 99%